Social medicine in brazil: an alliance between sanitary education and popular pedagogy - Souza, Ricardo Abussafy De [UNESP]; França, Sonia Aparecida Moreira [UNESP] (Associação Brasileira de Psicologia Social, 2013)
This study unfolds from the analysis of a set of documents collected during my doctoral research, which investigated the management of filth and its relationship with the governing of populations during the formation and development of modern cities. In this set, annals of Brazilian hygiene congresses, conducted during the first half of the twentieth century, a period characterized by the enlargement of techniques and practices of social medicine, were selected. Such annals of congresses and some laws of the time evidence the construction of an alliance between Sanitary Education and techniques of popular pedagogy, responsible for the population adherence to standards of conducts countersigned in social hygiene requirements. From Michel Foucault's writings on genealogical analysis, descent lines are described about healthy modes of conduct which, in turn, produce some effects in contemporary truth about personal and social hygiene.

Este estudo é desdobramento da análise de um conjunto de documentos coletados durante minha pesquisa de doutorado, em que se investigou sobre a gestão das imundícies e sua relação com o governo das populações durante a formação e desenvolvimento das cidades modernas. Neste conjunto, foram selecionados anais de congressos brasileiros de higiene, realizados durante a primeira metade do século XX, período caracterizado pela ampliação de técnicas e práticas de medicina social. Estes anais de congressos e algumas legislações da época evidenciam a construção de uma aliança entre Educação Sanitária e técnicas da pedagogia popular, responsáveis pela adesão da população a padrões de condutas referendadas em preceitos de higiene social. A partir dos escritos sobre análise genealógica de Michel Foucault, descrevem-se linhas de proveniências sobre os modos de conduta saudáveis e que, por sua vez, produzem na contemporaneidade alguns efeitos de verdade sobre higiene individual e social.
Medicina social no Brasil: uma aliança entre educação sanitária e pedagogia popular
Keywords: social medicine; sanitary education; popular pedagogy; genealogy; medicina social; educação sanitária; pedagogia popular; genealogia